Influence of nano-SiO2 on properties of fresh and hardened high performance concrete: A state-of-the-art review. (1st September 2017) - Zhang, Peng; Wan, Jinyi; Wang, Kejin; Li, Qingfu
Highlights: 83 papers are reviewed on high performance concrete (HPC) containing nano-SiO2 . Effect of nano-SiO2 on the fresh properties of HPC is discussed. The mechanical properties and durability of HPC are also addressed. Influence of nano-SiO2 on the microstructure of HPC is reviewed. Abstract: Application of nano-SiO2 (NS) particles to reinforce high performance concrete (HPC) has received widespread attention from both construction industry and researchers due to their interface improving effect, small size effect, filling effect and surface effect. This paper critically reviews previous research carried out on the effect of NS on properties of HPC. Detailed review on the fresh properties, mechanical properties and durability of high performance concrete containing NS particles are presented. Through 76 recent and past literatures, the influence of SiO2 nano-particles on workability and setting time of fresh mixture, compressive strength, flexural properties, fracture properties, water anti-permeability, chloride permeability, abrasion resistance, frost resistance, water absorption capacity, resistance to high temperatures and microstructure of HPC is discussed in this paper. The properties of NS modified concrete are compared with control concrete. Furthermore, this paper presents on the benefits and advantages to improve the HPC by using NS. It is shown that, in general, the incorporation of SiO2 nano-particles significantly improves the mechanical properties and durability of HPC though the flowability of the fresh concrete is decreased by the usage of NS. This literature review also aims to provide a comprehensive insight into possible application of NS modified concrete in the construction industry today.